2009
DOI: 10.1002/pmic.200700839
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to the protein profile of bladder carcinoma cell lines induced by plant extract MINA‐05 in vitro

Abstract: Bladder cancer (BLCa) is a severe urological cancer of both men and women that commonly recurs and once invasive, is difficult to treat. MINA-05 (CK Life Sciences Int'l, Hong Kong) is a derivative of complex botanical extracts, shown to reduce cellular proliferation of bladder and prostate carcinomas. We tested the effects of MINA-05 against human BLCa cell sublines, B8, B8-RSP-GCK, B8-RSP-LN and C3, from a transitional cell carcinoma, grade IV, to determine the molecular targets of treatment by observing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…41 Studies in cancerous cells have shown that bioactive extracts of plant inhibit cell proliferation through alterations in cell cycling, energy metabolism proteins, and ultimately the cancer cell environment. 42,43 Concomitantly, in the present study, with the increase in the duration of exposure, there was a reduction in cell growth with apparent morphological changes in extracts treated HT-29, Jurkat, T24, MIAPaCa-2, MCF-7, and HeLa cells. Their growth was noticeable in a more disperse manner with progressive accumulation of b-gal stain after attaining senescence at 48 hours (Figure 5).…”
Section: Discussionsupporting
confidence: 67%
“…41 Studies in cancerous cells have shown that bioactive extracts of plant inhibit cell proliferation through alterations in cell cycling, energy metabolism proteins, and ultimately the cancer cell environment. 42,43 Concomitantly, in the present study, with the increase in the duration of exposure, there was a reduction in cell growth with apparent morphological changes in extracts treated HT-29, Jurkat, T24, MIAPaCa-2, MCF-7, and HeLa cells. Their growth was noticeable in a more disperse manner with progressive accumulation of b-gal stain after attaining senescence at 48 hours (Figure 5).…”
Section: Discussionsupporting
confidence: 67%
“…Differential global proteomic technologies provide a broad signature of changes in protein levels which allow identification of key pathways and mechanisms responsible for complex biological effects [8, 9]. Despite advancements in mass spectrometry based proteomic techniques to understand biological processes at the molecular level, only a limited number of studies have used proteomics to study mechanisms by which botanicals induce biological effects [1013]. …”
Section: Introductionmentioning
confidence: 99%
“…The five different immunoconjugates of primary antibody (MIL38-BHHBTEGSB x , x = 7, 16,27,34,40) were tested in immuno-staining of cancer cell lines, using DU145 cells as positive control (GPC1+) and C3 bladder cancer cell line that does not express MIL38 antigen (GPC1-), 38,39 as negative control. The stained cells were inspected under TGL and conventional epifluorescence mode using a DAPI filter set.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%